Innovative lumped-battery model for state of charge estimation of lithium-ion batteries under various ambient temperatures. (1st July 2021) - Seo, Minhwan; Song, Youngbin; Kim, Jake; Paek, Sung Wook; Kim, Gi-Heon; Kim, Sang Woo
Abstract: Ambient temperature alters properties of lithium-ion batteries and affects the accuracy of estimation of state of charge (SOC), which is an important function to ensure the safety and reliability of electric vehicles. An accurate SOC estimation is critical under various temperatures. The existing methods have two problems: 1 ) need to perform time-consuming pre-experiments to investigate influence of various temperatures on the battery properties, and 2 ) use of the Thevenin model which is inaccurate at sub-zero temperatures. This study proposes an innovative lumped-battery model to improve the accuracy of both SOC estimation and battery modeling without pre-experiments. Two main causes of modeling errors by the Thevenin model are analyzed. Proposed model parameters are estimated using the recursive least squares, and the extended Kalman filter is used to estimate SOC in real time. Experiments are conducted under time-invariant and time-varying temperature conditions ranging from −10 °C to 30 °C. The results indicate that relative errors of battery modeling are less than 2.4% and that estimation errors of SOC are at most 0.4% under various temperatures. Therefore, the proposed method can be conveniently and widely applied to all-climate battery management systems to achieve a high accuracy of SOC estimation. Highlights: A novel battery model considering ambient temperature change is introduced. Pre-tests for battery properties varying with temperature are no longer necessary. Experiments under time-invariant and time-varying temperatures are conducted. Accuracy of battery modeling and SOC estimation is significantly improved.